Individualized Assessment and Therapeutic Intervention for Mental Health of American Postmodern Novelists - Ningxia Qu (Hindawi-Wiley, 2022)
Objective. Therapeutic intervention can improve the overall level of mental health of American postmodern fiction writers by improving their social communication skills and overall well-being. This paper discusses the application of art therapy in the mental health education of American postmodern novel creators and proves that expressive art therapy intervention is effective in improving the mental health level of American postmodern novel creators. Method. This article attempts to help American postmodernist novel creators understand their own mental health status by means of individualized assessment and therapeutic intervention and to analyze and discover their own potential mental health problems. The writers of postmodernist novels in the USA were measured and screened by means of scales and questionnaires, and the members who met the experimental intervention were divided into experimental group and control group, and the experimental group received a 30-day reception music therapy intervention. After the intervention, the data will be counted, and the quantitative and qualitative aspects will be analyzed to comprehensively evaluate the effect of the intervention. Results/Discussion. Receptive music therapy intervention has a significant effect in relieving the anxiety of American postmodernist novel creators and plays a positive role in helping American postmodernist novel creators better adapt to study life and build good emotional psychology and interpersonal relationships. Psychological counseling relies more on external forces to correct cognition and adjust psychology, while music therapy intervention, as a nonsemantic art, can arouse inner functions and mobilize the self-healing potential of American postmodern novel creators. Practice has proven that when the language intervention of traditional psychotherapy encounters resistance and silence, music as a special language plays a vital role. The nonlinguistic nature of music, through a mode of reproduction of sounds in nature, makes the beautiful and soothing melody stimulate a pleasant and peaceful psychological experience through human hearing.